MappingThe Landscape of Game-Based Cultural Diplomacy: A Bibliometeric Analysis of Global Trends and Influential Research - Azis, Muhammad Abdul; Angelina, Nadia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Video games are becoming an important part of cultural diplomacy. They let countries show off their national identity and soft power around the world. In the past, Japan and Poland have utilized video games to spread their cultural values and get along better with other countries. For instance, Japan's